2019
DOI: 10.1111/edt.12523
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory and anti‐resorptive efficacy of adrenergic blockers on late replanted rat incisors

Abstract: Background/Aim: In addition to their anti-inflammatory and anti-osteoclastogenesis properties, adrenergic blockers may also have promising anti-resorptive effects that can prevent root resorption when teeth are replanted because of avulsion. The aim of this study was to investigate the effects of phentolamine (Ph) and propranolol (Pr) in gels on the repair process of late replanted rat incisors. A further aim was to evaluate the biocompatibility of both drugs to human periodontal ligament fibroblasts (HPDLFs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
3
2
0
Order By: Relevance
“…However, when evaluated with histological and micro computerized tomography, they showed that there was no significant bone healing in rats. 17 In these studies, similar to our study, the effect of using different doses of systemic propranol on bone healing and osseointegration was not found. Although not clinically applied, reverse torque analysis was used to evaluate implant stability and osseointegration.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, when evaluated with histological and micro computerized tomography, they showed that there was no significant bone healing in rats. 17 In these studies, similar to our study, the effect of using different doses of systemic propranol on bone healing and osseointegration was not found. Although not clinically applied, reverse torque analysis was used to evaluate implant stability and osseointegration.…”
Section: Discussionsupporting
confidence: 87%
“…Matos et al in their study reported that propranol caused a significant decrease in the number of osteoclasts detected by tartrate-resistant acid phosphatase staining. However, when evaluated with histological and micro computerized tomography, they showed that there was no significant bone healing in rats 17 . In these studies, similar to our study, the effect of using different doses of systemic propranol on bone healing and osseointegration was not found.…”
Section: Discussionsupporting
confidence: 84%
“…However, at higher concentrations (≥10 µg/mL), phentolamine significantly triggered the death of MRC-5 cells. Related studies have demonstrated that high doses of phentolamine cause cytotoxicity both in vitro and in vivo [15,16]. Additionally, we found that phentolamine significantly ameliorated LPS-induced embryonic lung cell death in vitro.…”
Section: Discussionsupporting
confidence: 67%
“…One of the advantages of the delayed replantation of the avulsed tooth model is that PDLs can be completely necrotized by air drying for 1 h, while damage to alveolar bones can be minimized. [ 75 ] The other advantage is that the occlusal force can be controlled by altering the food structure (feeding with jelly or solid feed). [ 76 ] To establish the delayed replantation of the avulsed tooth model, the maxillary left incisor was first extracted from the tooth fossa, and then the extracted incisor was air‐dried in a fume hood for 60 min to ensure complete necrosis of the PDLs.…”
Section: Resultsmentioning
confidence: 99%
“…IACUC‐20221241). Based on previously published methods, [ 75 , 86 ] animals were anesthetized by the intraperitoneal injection of 0.1% pentobarbital sodium (0.4 mL/100 g). After general anesthesia, the maxillary left incisors of rats were submucosally anesthetized using primacaine (Acteon Pharma, Bordeaux, Gironde, France), and then the maxillary left incisor of each rat was completely extracted with minimum trauma using a 1# Root Elevator (BONEWELL Medical, Suzhou, Jiangsu, China).…”
Section: Methodsmentioning
confidence: 99%